Factors Influencing the Implementation of the Health Promoting University Initiative: Experiences of Ibero-American Universities - Suarez-Reyes, M (Oxford University Press, 2021)
The Health Promoting University (HPU) concept encourages universities to incorporate health into the university context. HPU initiatives exist worldwide, yet information on how universities translate the HPU concept into actions is scarce. This study aimed to identify the factors influencing the implementation of HPU initiatives in Ibero-American universities. Semi-structured interviews were held with seventeen representatives of universities in Ibero-America that had implemented an HPU initiative. All interviewees had been involved in the initiative and had occupied a position of responsibility for at least 1 year before the study. The interviews were carried out remotely, and the data were analyzed using an inductive approach. The main factors influencing the implementation of an HPU initiative were political support by the university authorities, coordination structure, funding, collaboration inside and outside university and participation of the university community. Among them, political support by the university authorities was considered the most important, although some initiatives succeeded without it and managed to obtain support during the implementation process. This study is one of the first to investigate the factors influencing the implementation of the HPU concept. A better understanding of these factors would enable universities to address them to develop the HPU initiative in the best possible conditions. © 2021 The Author(s) 2021. Published by Oxford University Press. All rights reserved. For permissions, please email: journals.permissions@oup.com.
Keywords: healthy university; whole university; settings approach; qualitative study